4CPS-245 Implementing clinical pharmacy practices in the comprehensive geriatric assessment performed by the mobile geriatric multidisciplinary team in orthopaedic units. (2nd March 2018) - Capelle, H; Hache, G; Caunes, P; Poletto, N; Bertault-Peres, P; Villani, P; Argenson, JN; Tropiano, P; Daumas, A; Honoré, S
Abstract : Background: Inappropriate polypharmacy in the elderly is a major health issue, associated with adverse clinical outcomes, especially iatrogenic, that can lead to hospitalisation. In the orthopaedic unit, the mobile geriatric multidisciplinary team (MGMT) is consulted to assess clinics of patients over 75 years. Recently, we have integrated pharmacist-lead systematic medication reconciliation with the geriatric comprehensive assessment performed by the MGMT. Purpose: The aim of our study was to evaluate the impact of medication review made by MGMT on in-hospital and post-discharge facilities' prescriptions, re-hospitalisation rate and mortality 1 to 3 months after discharge. Material and methods: We conducted a retrospective study on patients over 75 years, with a TRST score 2 and hospitalised in orthopaedic units 4 months before (September to December 2016) and 4 months after (January to April 2017) implementation. We compared therapeutic plans suggested by the MGMT and their acceptance rate. Cumulative exposure to anticholinergic and sedative drugs within the chronic treatment was measured by the drug burden index (DBI). Post-discharge adherence to the treatment plan was assessed by a phone call to physicians 4 to 7 days after discharge. Re-hospitalisation rate and mortality were assessed by phone calls 1, 2 and 3 months after discharge. Results: Fifty-eight and 56 patients were recruited before and after implementation, respectively. Demographics were comparable for both groups. 3.4±2.2 therapeutic recommendations per patient were made after implementing the process vs 2.0±1.7before (p<0.05). Their acceptance rate significantly increased: 53%±38% before vs 71%±29% after implementation (p<0.05). The DBI of chronic treatment was significantly decreased at discharge 0.81±0.58 vs 1.09±0.72 upon admission (p<0.01). For the patients included after implementation, the re-hospitalisation rate and the mortality were 12.5% 3 months after discharge, and, in rehabilitations facilities, physicians of 58% patients were aware of suggested treatment plans and applied 94%±0.1% of the recommendations. Physicians of 42% patients did not receive treatment plans but their therapeutic interventions covered 59%±35% of our suggestions (p<0.01). Conclusion: Implementing clinical pharmacy practices in the assessment provided by the MGMT in orthopaedic units significantly increased therapeutic recommendations such as their acceptance rate. Cumulative exposure to anticholinergic and sedative drugs significantly decreased at discharge for patients included after implementation. Adherence to the treatment plan is significant in post-discharge facilities when physicians are aware of it. We now focus on ensuring the transmission of treatment plans to improve MGMT's impact after discharge. No conflict of interest